Prospects of liquid biopsy in the prognosis and clinical management of gastrointestinal cancers - Mondal, Deepankar; Shinde, Sapnita; Sinha, Vibha; Dixit, Vineeta; Paul, Souvik; Gupta, Rakesh Kumar; Thakur, Suresh; Vishvakarma, Naveen Kumar; Shukla, Dhananjay (Frontiers in Molecular Biosciences, 2024)
Gastrointestinal cancers accounts for one fourth of global cancer incidence and incriminated to cause one third of cancer related deaths. GI cancer includes, esophageal; gastric; liver; pancreatic and colorectal cancers, and mostly diagnosed at advanced stages due to lack of accurate markers for early stages. Invasiveness of the diagnostic methods like colonoscopy for solid biopsy invites less patient compliance as it cannot be frequently used to screen the patients. Therefore minimally invasive approaches like liquid biopsy may be explored for screening and early identification to gastrointestinal cancers. Liquid biopsy involves qualitative and quantitative determination of certain cancer-specific biomarkers in body fluids such as blood, serum, saliva, urine etc. to predict disease progression, therapeutic tolerance, toxicities and recurrence by evaluating minimal residual disease and its correlation with other clinical features. In this review, we deliberate upon various tumor specific cellular and molecular entities such as circulating tumor cells (CTCs), tumor educated platelets (TEPs), circulating tumor DNA (ctDNA), cell free DNA (cfDNA), exosomes, exosome derived biomolecules and cite recent advances pertaining to their use in predicting disease progression, therapy response or risk of relapse. We also discuss technical challenges for liquid biopsy to be translated into clinical settings for varied clinical applications in gastrointestinal cancers.